Description of Student Response on The Implementation of Cooperative Learning Models of Jigsaw and Role Playing on The Physics Learning - Astalini, A.; Kurniawan, D. A.; Darmaji, D.; Erika, E.; Hoyi, R.; Sukarni, W. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2021)
Education is a conscious effort through planning that is prepared by considering various aspects that are important for developing student potential. One of the efforts can be made is implementing a cooperative learning model. This study aims to determine the differences in the results of the application of the Jigsaw cooperative learning model and role playing in physics as well as student responses to the application of the two learning models. This research procedure uses mixed methods using quantitative data obtained by questionnaires, qualitative data is obtained by conducting interviews. The results showed that there were still many students who responded well to the application of the jigsaw cooperative learning model in learning physics but in contrast to student responses to role playing learning. This study aims to determine student responses to the implementation of the Jigsaw cooperative learning model and role playing in physics subjects and to determine the differences in the application of those two models in physics subjects. The novelty of this study is to describe student learning outcomes with the physics learning process and student responses when using the jigsaw cooperative learning model and the role-playing model in physics to make it easier for students to learn and understand concepts and formulas in physics learning. The results showed that many students responded to the application of the jigsaw cooperative learning model and the role-playing learning model in physics learning well. The novelty of this research is that it can improve students' attitudes towards physics by using the jigsaw cooperative learning model and the role playing model.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â